Daily survey participation and positive changes in mental health symptom scores among Royal Canadian Mounted Police Cadets - Shields, Robyn E.; Teckchandani, Taylor A.; Asmundson, Gordon J. G.; Nisbet, Jolan; Krakauer, Rachel L.; Andrews, Katie L.; Maguire, Kirby Q.; Jamshidi, Laleh; Afifi, Tracie O.; Lix, Lisa M.; Brunet, Alain; Sauer-Zavala, Shannon; et al. (Frontiers in Psychology, 2023)
Royal Canadian Mounted Police (RCMP) officers self-report high levels of mental health disorder symptoms, such as alcohol use disorder, generalized anxiety disorder, major depressive disorder, panic disorder, and posttraumatic stress disorder. Participation in regular mental health monitoring has been associated with improved mental health symptom reporting and may provide an accessible tool to support RCMP mental health. The current study assessed relationships between self-reported mental health symptoms and the completion of daily surveys (i.e., daily mental health symptom monitoring) by RCMP cadets during the Cadet Training Program (CTP). Participants were RCMP cadets (n = 394 cadets; 76.1% men) who completed the 26-week CTP and daily self-monitoring surveys, as well as full mental health assessments at pre-training (i.e., starting the CTP) and pre-deployment. Symptoms of alcohol use disorder, generalized anxiety disorder, major depressive disorder, panic disorder, and posttraumatic stress disorder were assessed. Spearman’s rank correlations were estimated for number of daily surveys completed and change in mental health symptom scores between pre-training and pre-deployment. There were statistically significant negative relationships between number of daily surveys completed and change in mental health symptom scores; specifically, cadets who completed more daily surveys during CTP reported fewer symptoms of AUD, GAD, MDD, PD, and PTSD. Participation in daily mental health monitoring was associated with improvements in self-reported mental health symptoms between pre-training and pre-deployment. Regular self-monitoring of mental health symptoms may help to mitigate mental health challenges among RCMP cadets and officers.